Needs Analysis of The Development STEM-PjBL Based LKPD To Train Students' Critical Thinking Skills - Jeliana Veronika Sirait; Rizki Maulida (Universitas Riau, 2023)
Critical thinking skills is very important in the science learning process. Teaching materials are needed to encourage critical thinking skills. This research was conducted to analyze the needs of teachers and students for the development of STEM-PjBL based LKPD to train students’ critical thinking skills. The research method used was descriptive to investigate the initial conditions. The research data was collected using an interview sheets and distributing needs analysis questionnaires through google form. The subjects of this study were physics teacher and 25 students of class XI IPA SMA in Tebing Tinggi. The datas were analysis using qualitative analysis techniques. The results showed that: (1) teachers had never used STEM-PjBL based LKPD before, (2) students were not familiar with learning activities that require critical thinking skills and they have difficulty in understanding the use of physics formulas, (3) students and teachers agree with the development of STEM-PjBL based LKPD to train critical thinking skills.